Avaliação da sensibilidade à dor nos membros inferiores de mulheres corredoras de curta distância e sua relação com as variáveis de treinamento da corrida: estudo transversal comparativo - Mota, Riziane Ferreira da (2024)
Introduction: Running is one of the most practiced sports in the world and women are increasingly taking part in the sport. Despite this, pain and injuries are common among practitioners, therefore, advance risk monitoring strategies are necessary. Objectives: to evaluate, primarily, the relationship between the volume, pace and time of running practice and pressure pain threshold (LDP) measurements in the lower limbs (LL) of short-distance runners and, secondarily, to understand the differences or similarities of LDPs in relation to male short- distance runners and female non-runners. Methods: This is a comparative cross-sectional observational study whose main population was female short-distance runners and the comparison populations: 1. male short-distance runners; 2. non-runner women. 82 individuals between 20 and 54 years old, of both sexes, were included, 33 women and 23 men short-distance runners (≤ 10 km), with at least 3 months of practice and 15 km of weekly training volume; and 26 non-runners (time ≥ 3 months without physical exercise). Anthropometric data and LDPs were collected on the greater trochanter of the femur, piriformis muscle, quadriceps tendon and anterior tibialis muscle of all participants using a portable pressure algometer (Impac®, Paulínia, SP, Brazil). Additionally, the runners completed the training/race routine monitoring form. Statistical analyzes were performed in SPSS Statistics V25.0 and considered p <0.05. Normality and homogeneity were tested by Shapiro-Wilk and Levene, respectively. For comparisons, the Mann-Whitney and Kruskal-Wallis tests were applied, followed by the Wilcoxon post-hoc test. For correlations, the Spearman test was used, followed by regression analyses. Results: The regressions showed that when increasing weekly volume by 1 km, the LDP of the left trochanter (B = 0.094, 95% [CI = 0.004 – 0.185]) increases by 0.094 kgf/cm2. Furthermore, when increasing running pace, the LDP of the left trochanter increases by 0.90 kgf/cm2, and with an increase of one year in practice time, the LDP of the right and left tibialis anterior muscle increases by 0.30 and 0.37 kgf/cm2, respectively. Male runners had a higher running pace than women (U = 128.500; z = -4.187; p = 0.000; r = -0.56), whereas women had a longer training duration (U = 225.500; z = - 2.572; p= 0.010; r =-0.34). The LDPs of the trochanter and piriformis region were significantly higher in men than in women runners and non-runners, although between them (runners and non-runners) there was no significant difference in any of the variables. Conclusion: The practice of running appears to be unrelated to mechanical hyperalgesia in the lower limbs of female runners; on the contrary, there is an increase in LDPs with increasing volume, pace and running time, especially in the hip region. Men demonstrated higher LDPs in the hip region, however, they had a higher running pace.